Pelatihan pengolahan koran bekas menjadi karya kreatif bernilai ekonomis tinggi - Harsani; Yusriadi; Rasbawati (P3HKI - Universitas Muhammadiyah Parepare, 2023)
Training on processing used newspapers into creative works of high economic value is an innovative step to overcome the problem of waste accumulation and develop local economic potential. Used newspapers, which were previously considered waste, became the focus of this training. Students from the Muhammadiyah Student Association (IMM) A. R. Fachruddin Muhammadiyah University of Parepare were involved in the training process, enabling them to explore their skills and creativity in turning used newspapers into attractive photo frames. Training and mentoring methods, through a participatory model with lectures, discussions, and direct practice, strengthen the application of science and technology to students. The results of the activity show an increase in students' understanding of waste utilization, creating creative products, and applying design concepts that include safety, comfort, and beauty. This activity also encourages entrepreneurial awareness among students, making them potential drivers of the local economy. Empowerment through creativity in managing used newspapers provides solutions to environmental problems and improves the student economy. In conclusion, this training not only changed the view towards waste but also opened up new opportunities in creating high-value products from previously neglected resources.